Esterase activities of indigenous lactic acid bacteria from Argentinean goats' milk and cheeses - Oliszewski, Ruben (2007)
Esterase activities of indigenous lactic acid bacteria isolated from goats' milk and cheese were investigated. All of the strains exhibited esterase activity on α-naphthyl derivative of fatty acids of 2-6 carbon atoms. Lactobacillus fermentum ETC1 and L. bulgaricus ETC2 showed the highest specific activity on α-naphthyl acetate; L. rhamnosus ETC14 presented the highest specific activity on α-naphthyl butyrate and caproate. All enterococci strains presented the highest specific activities on α-naphthyl propionate, butyrate and caproate, and the lowest specific activities on α-naphthyl acetate. Pedicoccus pentocaseus ETC5 only had esterase activity on α-naphthyl acetate. The electrophoretic zymogram showed for each strain an individual enzyme profile on α-naphthyl acetate and revealed the presence of more than one esterase. L. plantarum ETC11 and Enterococcus faecium ETC9 showed four and five bands of esterase activity, respectively. The strains evaluated in this work showed different esterase activities, which were species and strain specific.